The promises and pitfalls of global digital food systems - Cook, Simon; Jackson, Elizabeth (2019)
The world is going digital; agriculture is following suit. It started some way behind but is catching up fast, and AgTech developers are witnessing major new investor interest. Like all growth spurts, this is an exciting but uncertain process that is prone to hype. The difference between hype and sustained growth is in the narrative - a realistic narrative, based on plausible growth expectations and an understanding of change, will sustain the inevitable obstacles that lie ahead. In this paper we aim to reduce the risk of growth by explaining the fundamental role for digital technology to support sustainable global food chains through to 2050 and beyond. Using a food chain concept, we identify how change is likely to occur and some of the pitfalls that await us.